Pengukuran Tingkat Efisiensi Bank Syariah dan Bank Konvensional di Indonesia dengan Formula David Cole’s Roe For Bank - Bachruddin Bachruddin (Jurnal Siasat Bisnis, 2006)
This research was aimed to analyze the difference in the rate of efficiency between the group of Syariah Bank with the group of conventional Banks in Indonesia during 2003 and 2004. To analyze the rate of efficiency indicated by the Rate of Return (ROE), the research uses three factors namely Profit Margin (PM), Asset Utilization (AU) and Equity Multiplier (EM). The research was based on secondary data consisted of finan¬cial reports collected from the said two group of banks, comprising 4 Syariah Bank and 4 Conventional Banks, for the period of 2003 and 2004.The tools of analysis used in the research consisted of two methods. The first was variance test analy¬sis for the average of ROE between the two groups of banks. The second was regression analysis applied for each group of banks. In this model, the factors i.e. PM, AU and EM were estimated to influence the ROE.The result of the research showed that the ROE of Syariah Bank was significantly difference with the ROE of Conventional Banks. In this result the standard deviation of ROE of Syariah Banks was smaller than con¬ventional banks. Further, the result indicated that PM, AU and EM of Syariah Bank were significantly influenced to ROE. Meanwhile, the three factors were not significantly influenced to ROE of Conventional Banks.In order to get the better result in the next research of this topic, the number of samples should be greater and it is suggested to apply the other method of analysis like discriminate analysis. Further, the period of empirical study should be longer at least five years.Keywords: rate of efficiency, profit margin, asset utilization, equity multiplier, bank syariah